(untitled) (SCIENCE TIME JOURNAL, 2026)
Reading instruction at the A1 level is a crucial stage in foreign language education, as learners develop basic decoding, word recognition, and initial comprehension skills. Traditional teacher-centered approaches often limit learner engagement, whereas interactive, learner-centered instruction promotes active participation and meaningful text interaction. This article presents an informative analysis of an interactive approach to teaching reading skills to A1 learners. Drawing on contemporary research, it examines pedagogical principles and instructional practices that support reading development, motivation, and learner autonomy at the beginner level.